Identification of Two New Isolates of Chilli veinal mottle virus From Different Regions in China: Molecular Diversity, Phylogenetic and Recombination Analysis - Rao, Shaofei; Chen, Xuwei; Qiu, Shiyou; Peng, Jiejun; Zheng, Hongying; Lu, Yuwen; Wu, Guanwei; Chen, Jianping; Jiang, Wen; Zhang, Yachun; Yan, Fei (Frontiers in Microbiology, 2020)
Chilli veinal mottle virus (ChiVMV) is an important plant pathogen with a wide host range, causing serious yield losses in pepper production all over the world. Recombination is a major evolutionary event for single-stranded RNA viruses, which helps isolates adapt to new environmental conditions and hosts. Recombination events have been identified in multiple potyviruses, but so far, there have been no reports of recombination events among the ChiVMV population. We here detected ChiVMV in pepper samples collected from Guangxi and Yunnan provinces for the first time and amplified the nearly full-length sequences. Phylogenetic and recombination analysis were performed with the new sequences and the 14 full-length and 23 Capsid Protein (CP) sequences available in GenBank. Isolates tend to cluster on a geographical basis, indicating that geographic-driven evolution may be an important determinant of ChiVMV genetic differences. A total of 10 recombination events were detected among the ChiVMV sequences using RDP4 with a strict algorithm, and both the Guangxi and Yunnan isolates were identified as recombinants. Recombination appears to be a significant factor affecting the diversity of ChiVMV isolates.